Increased fruit load influences vegetative growth, dry mass partitioning, and bean quality attributes in full-sun coffee cultivation - León-Burgos, Andrés Felipe; Sáenz, José Raúl Rendón; Quinchua, Luis Carlos Imbachi; Toro-Herrera, Mayra Alejandra; Unigarro, Carlos Andrés; Osorio, Valentina; Balaguera-López, Helber Enrique (Frontiers in Sustainable Food Systems, 2024)
Coffee fruits are highly competitive compared to other functional sink organs. This can affect the vegetative growth of the shoot, dry mass partitioning, and the size and amount of healthy beans. Therefore, this research aimed to evaluate changes in vegetative growth, physical and sensory attributes of the coffee bean, and total crop yield in response to varying fruit load at the tree level established under full-sun cultivation. The experiment was carried out for two consecutive years under field conditions with coffee trees of the cultivar "Cenicafé 1". Nine different fruit load intensities at the whole-plant level of 20, 30, 40, 50, 60, 70, 80, 90, and Con formato: Inglés (Estados Unidos) 100% were evaluated. The vegetative growth of leaves and branches, leaf area-to-fruit ratio, and dry mass accumulation were evaluated, and growth indices were calculated. Total coffee fruit production, size and distribution of healthy beans, and sensory analysis were determined. As expected, for coffee trees with a 100% fruit load, we found significant decreases in the total number of leaves, leaf area-to-fruit ratio, and branch growth; less dry mass allocated to leaves and branches with a negative correlation between this and the fruit dry mass accumulation; and lower distribution of large and healthy beans. Unexpectedly, annual and accumulated patterns of total production and sensory quality of coffee beverage were not affected by the high fruit load. The findings suggest that increased fruit load in coffee trees of the "Cenicafé 1" variety led to changes in vegetative growth, dry mass partitioning, and physical quality of the beans. However, there was no impact on production patterns and sensory attributes.